Clean technology and the environment: Key issues and implications in belt and road initiative economies - Nanli, Zhu; Xiaoping, Li; Sohail Akhtar, Muhammad; Bilal, Ahmer (Frontiers in Environmental Science, 2022)
China has planned the Belt and Road Initiative to start collaborations among relevant economies in the technology innovation sector. This study examined the impact of technology innovation on environmental quality among the host economies of Belt and Road Initiative (BRI) countries by using panel data of 45 economies from 1991 to 2019. The study employed a fully modified ordinary least squares (FMOLS) panel to estimate the long-run associations among suggested variables. The outcomes validated a healthy cross-sectional dependence within the panel BRI economies. One estimated result of FMOLS specified that increases in patents and trademarks improved the quality of the environment in only Europe in the long run. Trademarks also enhanced the environment in BRI, MENA, and Central Asia. In the short run, the panel heterogeneous causality showed bi-directional causality among patents, trademarks, and CO2 emissions. The results of this study articulated the environment-friendly policies in technology innovation in BRI regions.